Biological determinants outweigh the learning environment: a path-analytic model of physical fitness, nutritional status, and motor ability in primary-school children - Ridho Guswandi; Masrun Masrun; Khairuddin Khairuddin; Donie Donie (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Motor skills in the middle childhood phase are a critical skill through which one could attain lifelong physical activity; However, their determinants are often examined separately, which "hides" the fact of how biological readiness and the instructional environment together influence movement outcomes. Objective: In this work, the authors represented the direct and indirect impacts of children's motor ability through physical fitness, nutritional status, and the learning environment in such a way that the learning environment was considered as a mediator. Methods: The research was carried out using a cross-sectional, correlational design on 38 fifth-grade pupils at a laboratory primary school in Padang, Indonesia. Physical fitness was measured with the Indonesian Student Fitness and Skill Test (Phase C), nutritional status with body-mass-index-for-age, the learning environment with a validated Likert questionnaire, and motor ability with the Nurhasan Motor Ability Test. Data were analysed through path analysis using ordinary-least-squares regression across three structural models in IBM SPSS Statistics 27, after verifying normality, linearity, and the absence of multicollinearity. Results: Physical fitness is a great predictor of nutritional status (beta = 0.899, R-squared = 0.809). Net of confounds in the model, physical fitness (beta = -1.052), nutritional status (beta = 0.603), and the learning environment (beta = -0.299) each had a significant direct effect on motor ability, and all six hypotheses were supported. Learning environment transmission indirect effects were quite small (-0.432 and 0.193), suggesting that biological factors impacted primarily the motor ability through direct rather than mediated pathways. Conclusively, in an educationally homogeneous setting, children's physical fitness and nutritional status are the primary determinants of their motor ability, whilst the learning environment represents more of a facilitating than a mediating factor. Practical implication: Physical-education programmes should focus on fitness development and nutritional monitoring while continuing to offer a positive and supportive instructional atmosphere.